Inflation in Orange Juice Prices and Consumer Responses - Sungeun Yoon; Marisa Zansler; Lisa House (EDIS, 2024)
This publication examines the recent inflation in orange juice prices and consumer responses using Nielsen scanner and Orange Juice tracker datasets. Orange juice prices experienced high inflation, peaking at 14.1% in January 2023, leading to decreased sales in both volume and dollars. Consumers are aware of the ongoing inflation in orange juice prices and reduced their orange juice purchases in quantity and frequency instead of discontinuing consumption altogether. Despite the significant barrier of high prices, the proportions of active orange juice consumers and those with a positive perception of orange juice remained steady and strong. Marketing efforts emphasizing the health benefits of orange juice continue to be crucial in sustaining consumer perception and demand.